2021
DOI: 10.1111/dth.14650
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy profile of oral cyclosporine vs oral methotrexate vs oral acitretin in palmoplantar psoriasis: A hospital based prospective investigator blind randomized controlled comparative study

Abstract: Palmoplantar psoriasis (PPP) is a variant of psoriasis which affects only 5% body surface area, but has a devastating impact on affected individual's quality of life. There are few studies assessing efficacy of individual drugs, and few comparative studies of efficacy of two drugs in the literature, however randomized control trial comparing all three drugs against each other has not been done. A total of 75 patients of PPP were enrolled for study and randomly divided into three groups A, B, C of 25 each and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Methotrexate, cyclosporine and acitretin are drugs commonly used in the treatment of psoriasis; acitretin has a longer-lasting effect, and the effect of cyclosporine on lesions is faster, while methotrexate and acitretin have a similar effect [ 133 ]. However, these drugs can cause non-alcoholic fatty liver disease and liver fibrosis in obese patients when administered at high doses [ 45 ].…”
Section: The Link Between Psoriasis and Obesitymentioning
confidence: 99%
“…Methotrexate, cyclosporine and acitretin are drugs commonly used in the treatment of psoriasis; acitretin has a longer-lasting effect, and the effect of cyclosporine on lesions is faster, while methotrexate and acitretin have a similar effect [ 133 ]. However, these drugs can cause non-alcoholic fatty liver disease and liver fibrosis in obese patients when administered at high doses [ 45 ].…”
Section: The Link Between Psoriasis and Obesitymentioning
confidence: 99%
“…However, the severity of such AEs was generally dose-dependent and was successfully treated by symptomatic treatments, as previously reported by studies performed in China and other countries. 4,22,[24][25][26][27] The next most commonly affected systems/tissues were the endocrine and digestive systems, especially represented by dyslipidemia and elevated liver enzymes. AEs affecting the nerves, circulation, and mental status were less commonly reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that most patients have adverse reactions of varying degrees to acitretin. 13,[19][20][21][22] These adverse reactions are usually dose-dependent and reversible and can disappear or alleviate after dose reduction or initiation of intermittent therapy. 4,8 However, drug reduction or discontinuation due to adverse reactions is typical in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…7 Systemic agents including methotrexate, acitretin, and cyclosporine have all shown efficacy, however, the adverse side effects associated with the aforementioned agents makes their use disfavorable. 8 Side effects of apremilast, on the other hand, primarily consist of diarrhea and depression, which are typically…”
Section: Discussionmentioning
confidence: 99%